THE EFFECT OF BRAND IMAGE DECISIONS TO PURCHASE SILVERQUEEN CHOCOLATE IN PT.KOTA MAS PERMAI BRANCHES PEKANBARU (STUDY CASES OF OUTLETS SELLERS IN PANAM) - Dzikra, Faira Medina; Delia, Tiara Samia (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
This study aims to determine whether the brand image has an influence on purchace decisions to silverqueen chocolate in PT. Kota Mas Permai branches Pekanbaru. The samples in this study using a convenience sampling method. This population research study are outlets sellers in panam pekanbaru.73 questionnaires distributed and returned with a piece without being fell. The hypotesis tested in this test using a simple linear regression which tested using SPSS. Based on testing of 73 pieces the questionnaire, the researcher can conclude that the independent variable (brand image) has a significant influence on purchasing decisions. It can be seen from t is greater than t table ((8,796>1,667) ,with a large percentage of the influence of brand image on the purchese decisions of 52,1%